(untitled) (INTERNATIONAL JOURNAL OF IOT AND DATA SCIENCE (IJIDS), 2024)
This paper explores the innovative Delta Lake UniForm feature, which provides seamless interoperability between Delta Lake, Iceberg, and Hudi formats. By leveraging the latest advancements in Delta Lake 3.0 and UniForm, this paper delves into the technical intricacies of integrating multiple open table formats, optimizing performance, and ensuring robust data management and compliance. The paper also highlights the practical applications, benefits, and challenges of implementing Delta Lake UniForm in modern data architectures.